A forgotten risk factor for surgical site infection: Hypocholesterolemia - D., Manjunath B.; R., Harindranath H.; Razak, Abdul; Ali, Mohammed Arafath (International Surgery Journal, 2018)
Background: Postoperative infection is one of the most common complications after any surgery. In the present study, surgical site infection (SSI) is described as; superficial (i.e., skin and subcutaneous tissues) and deep (i.e., fascia and muscles) infections occurring in the short term (i.e., 1-month) after surgery. The objective of this study was to detect various risk factors for SSI development. Methods: In this study, we prospectively enrolled 217 patients undergoing spinal surgery over an 8 months period. In a prospective study from January 2017 to August 2017, 217 patients who were admitted and operated for elective hernia surgery in hospitals attached to Bangalore Medical College and Research Institute, patients with immunodeficiency disorders and obstructed hernias were excluded. Results: Of 217 patients 35 (16.12%) patients developed SSI, multi-variant data analysis indicated that multiple factors correlated with an increased risk of SSI of which one of the important factor was hypocholesterolemia with 32.8% people developing SSI with p-value <0.01 along with Hypoalbuminemia and diabetes. Whereas other factors shuch as age had a minor role in increasing the incidence of SSI other factors such as smoking, alcoholism, gender, hypertension was found not to have much significant contribution in the development of SSI in the present study. Conclusions: Hypocholesterolemia is one on the forgotten factors which is usually brushed aside whose consideration can lead to significant decrease in this preventable complication especially in a malnourished population presenting in a government setup.